Detailed analysis of biased histamine H4 receptor signalling by JNJ 7777120 analogues. (15th August 2013) - Nijmeijer, S; Vischer, H F; Sirci, F; Schultes, S; Engelhardt, H; de, C; Rosethorne, E M; Charlton, S J; Leurs, R
<x xml:space="preserve">Abstract</x> Background and Purpose The histamine H4 receptor, originally thought to signal merely through Gαi proteins, has recently been shown to also recruit and signal via β‐arrestin2. Following the discovery that the reference antagonist indolecarboxamide JNJ 7777120 appears to be a partial agonist in β‐arrestin2 recruitment, we have identified additional biased hH4R ligands that preferentially couple to Gαi or β‐arrestin2 proteins. In this study, we explored ligand and receptor regions that are important for biased hH4R signalling. Experimental Approach We evaluated a series of 48 indolecarboxamides with subtle structural differences for their ability to induce hH4R‐mediated Gαi protein signalling or β‐arrestin2 recruitment. Subsequently, a Fingerprints for Ligands and Proteins three‐dimensional quantitative structure–activity relationship analysis correlated intrinsic activity values with structural ligand requirements. Moreover, a hH4R homology model was used to identify receptor regions important for biased hH4R signalling. Key Results One indolecarboxamide (75) with a nitro substituent on position R7 of the aromatic ring displayed an equal preference for the Gαi and β‐arrestin2 pathway and was classified as unbiased hH4R ligand. The other 47 indolecarboxamides were β‐arrestin2‐biased agonists. Intrinsic activities of the unbiased as well as β‐arrestin2‐biased indolecarboxamides to induce β‐arrestin2 recruitment could be correlated with different ligand features and hH4R regions. Conclusion and Implications Small structural modifications resulted in diverse intrinsic activities for unbiased (75) and β‐arrestin2‐biased indolecarboxamides. Analysis of ligand and receptor features revealed efficacy hotspots responsible for biased‐β‐arrestin2 recruitment. This knowledge is useful for the design of hH4R ligands with biased intrinsic activities and aids our understanding of the mechanism of H4R activation. Linked Articles This article is part of a themed issue on Histamine Pharmacology Update. To view the other articles in this issue visit http://dx.doi.org/10.1111/bph.2013.170.issue‐1